The Rainwater Harvesting Movement: Between Myths, Religion, and Environmental Conservation - Siti Zunariyah; Nur Muhlashin; Zanisah Man; Faline Izza Nisa’u (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2026)
This article is situated within the field of environmental sociology and adopts an interdisciplinary approach that integrates religious, cultural, and water resource conservation dimensions. The aim of this study is to analyze the rainwater harvesting movement as a social practice that is not only technically and ecologically oriented but also shaped by the construction of myths and religious values within society. The significance of this topic lies in the understanding that the increasingly complex water crisis cannot be viewed solely as an environmental issue; it must also be recognized as a social phenomenon intertwined with value systems, power dynamics, and the daily practices of communities. This study employs qualitative methods, specifically a case study approach that includes field observations conducted in the Banyu Bening Community of Tempursari Hamlet, Sardonoharjo, located in the Ngaglik Subdistrict of Sleman Regency in the Special Region of Yogyakarta. The research also features in-depth interviews and narrative analyses of community practices and interpretations related to rainwater. The findings reveal that the rainwater harvesting movement has emerged from a tension between environmental conservation rationality, mythological beliefs, and the legitimization of religious values. While this practice serves as an adaptive strategy to confront the water crisis, its effectiveness is heavily influenced by how well religious values are internalized as ecological ethics that inspire collective action. This research contributes to strengthening the hydrosocial perspective within environmental sociology by identifying religion as a crucial factor in conservation practices. The findings emphasize the necessity of integrating local knowledge, religious values, and environmental policies to achieve sustainability. Consequently, this research provides an essential foundation for developing contextually relevant and sustainable conservation strategies that are deeply rooted in culture and religion.